Rancang Bangun Sistem Informasi Human Resources Development (HRD) di Vita Gym Berbasis Desktop - Hutagalung, Dini M; Zaneta Onliang; Manurung, Immanuel H G (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
This research focuses on the development of a Human Resources Development (HRD) information system for Vizta Gym, a fitness center with four branches in Medan, to improve the efficiency of human resource management that was previously done manually. The method used in system development is the Waterfall Model, which includes the stages of requirements, analysis, design, coding, and testing. The purpose of this research is to solve the problem of data integration between branches, minimize errors in managing employee data, and speed up the salary calculation process that was previously done manually. The results showed that the system developed was able to change the process of managing employee data to be more efficient and accurate, with features such as automation of salary calculations and generation of reports that help management in monitoring employee performance. This information system successfully overcomes difficulties in searching and verifying employee data and reduces the risk of errors in payroll, thereby increasing operational efficiency at Vizta Gym.